The Relationship Between Shallap Glacier - Cordillera Blanca and King George Island - Antarctic Peninsula - Rojas Macedo, I. C. (2021)
The main goal of this study is to determine the relationship between Shallap Glacier (SG) — Cordillera Blanca and King George Island (KGI) glaciers — Antarctic Peninsula and describe their features. Multi-temporal analysis with satellite imagery from 1989 to 2019 was made. The SG and KGI glaciers seem to be quite different. Nevertheless, preliminary results, in this research, show that approximately 74% of KGI glaciers have reduced their areas (below 20%) as same as the SG in the last 30 years. Indeed, SG (6 Km2) represents only 0.6% of the KGI glaciers (993.6 Km2), but each zone's different own factors seem to be shrinking glacier coverage at about similar proportions.